A RESEARCH AGENDA FOR CLIMATE AND CLIMATE-CHANGE IMPACTS ON EARTHEN STRUCTURES - Cooke, Louise; Brimblecombe, Peter (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
Climate change is likely to affect earthen-architectural heritage because the materials are sensitive to many aspects of weathering. Both gradual changes and an increase in the frequency of extreme events seem likely to be important in the future. Both represent threats to earthen materials, which can be especially sensitive to alterations in humidity and water. At the moment there is little research on the mechanisms of damage that might change over the next century. While there are many general questions that relate to future damage to our heritage, research has to be more speciic. The authors examine the potential for a ive-year test-wall project to explore climate-change issues. Walls would be designed to facilitate ease of repeat documentation using conventional and 3D methods. These qualitative and quantitative observations would be compared with measurements gathered through an on-site weather station and wall sensors (recording temperature and humidity). This in turn would be compared to the high-resolution climate models. The analysis would, we argue, start to give an indication of observed change, quantiied change and the relationship with climate over ive years, which in turn could be related to the longer-term climate models.